COVID-19 vaccination: 2023 Taiwan Association of Gerontology and Geriatrics (TAGG) consensus statements - Hao-Hsiang Chang; Yi-Hsuan Lee; Kuo-Chin Huang; Ding-Cheng Chan; Ying-Chin Lin; Wang-Huei Sheng; Long-Teng Lee; Li-Min Huang (Journal of the Formosan Medical Association)
The COVID-19 pandemic remains challenging due to the rapid evolution of the severe acute respiratory syndrome coronavirus 2. This article discusses recent findings on high-risk groups for COVID-19 mortality and morbidity, along with consensus statements from the 2023 Taiwan Association of Gerontology and Geriatrics (TAGG) meeting. It examines evidence on viral mutation mechanisms, emerging variants, and their implications for vaccination strategies. The article underscores advanced age, immunocompromised status, chronic medical conditions, occupational exposure, and socioeconomic disparities as significant risk factors for severe COVID-19 outcomes. TAGG's consensus emphasizes robust vaccination promotion, prioritizing elderly, and immunocompromised groups, individualized multi-dose regimens for immunocompromised patients, and simplified clinical guidelines. Discussions on global and regional recommendations for regular, variant-adapted boosters highlight the non-seasonal nature of COVID-19. Key agreements include escalating domestic preparedness, implementing vigorous risk-based vaccination, and adapting global guidelines to local contexts. Given ongoing viral evolution, proactive adjustment of vaccination policies is essential. Scientific consensus, tailored recommendations, and rapid knowledge dissemination are vital for optimizing COVID-19 protection among vulnerable groups in Taiwan. This article seeks to inform clinical practice and public health policy by summarizing expert-driven vaccination perspectives.